Perbandingan Belanja Pegawai, Hibah, dan Belanja Tak Terduga di Aceh: Studi Komparatif Masa Pandemi dan Pasca Pandemi - Rahmat Arfan; Safna Lia Rahman; Fitrian Rizky (MAMEN: Jurnal Manajemen, 2026)
This study aims to determine whether there are differences in employee spending, grant spending, and unexpected spending during and after the COVID-19 pandemic in Aceh. This study focuses only on districts/cities in Aceh Province. The research method is a comparative quantitative approach, using secondary data in the form of budget realization reports (LRAs) from the COVID-19 pandemic period (2020-2021) and the post-COVID-19 pandemic period (2022-2023). The data analysis technique used was a paired-samples difference analysis with the Wilcoxon signed-rank test to assess the significance of the differences between the two periods. The results indicate no difference in employee spending before and after the COVID-19 pandemic. This occurs because employee spending is routine, such as salaries and allowances, which must be paid periodically. However, different results were obtained for grant and unexpected spending, with differences both during and after the pandemic. This occurred because, during the pandemic, local governments required substantial reserve funds for emergency response, including purchasing medical equipment, providing social assistance, and supporting COVID-19 response operations. These funds then decreased after the pandemic subsided. This difference also reflects the government’s swift response to the pandemic, focusing on improving the community’s economy and addressing the pandemic within the community. Further research is expected to expand the sample size to provide a broader overview of employee spending, grant spending, and unforeseen expenses during and after the COVID-19 pandemic.